Depression, Anxiety and Sexual Dysfunction in Patients with Diabetes Mellitus With and Without Foot Ulcer - H, Husin; H, Sidi; A, Baharudin (IIUM Medical Journal Malaysia, 2017)
Introduction: Anxiety and depression are both associated with increased morbidity in diabetic population, especially those afflicted with foot ulcer, whereas Erectile Dysfunction (“ED”) and Female Sexual Dysfunction (“FSD”) are amongst the common complication found in diabetes. This study aimed to determine the prevalence of anxiety and depression as primary outcome and sexual dysfunction (“SD”) as a secondary outcome in diabetic patients with and without foot ulcer (“DFU”). Methods: A cross-sectional study was conducted in Hospital Raja Permaisuri Bainun Ipoh, Perak, where 164 diabetic patients were recruited for the purpose of this study. Hospital Anxiety and Depression Scale (“HADS”) were utilised to measure anxiety and depression. International Index for Erectile Function 5 (“IIEF-5”) and the Malay version of Female Sexual Function Index (“MVFSFI”) were used to detect SD. Simple and multiple logistic regressions were referred to in order to evaluate the factors associated with anxiety, depression and SD. Results: In the group with foot ulcer, 36.8% had depressive and anxiety risk respectively compared to without the foot ulcer, 37.5% and 38.5% respectively. Male gender (AOR=6.3,p=0.002,95%CI 1.975, 20.205) and having lower education status (AOR=6.0,p=0.018,95%CI1.36,26.59,) was associated with foot ulcer. High prevalence of SD found in foot ulcer group (52.6%,p=0.006). Those with depression (OR=4.421,95% CI 1.08,18.16,p=0.039) and male gender (OR=18.42,p<0.01,95%CI5.5,-61.62) predicts present of SD. Conclusion: Depression and anxiety prevalent were similar for both with and without diabetic foot ulcer. Several significant predictor factors were identified for DFU group, for anxiety and depression risk and for SD in a diabetes patient. Further studies are required to establish the directional nature of this relationship.